Religious denominations vs ethical models in the beginning of life (Bangladesh Journal of Bioethics, 2012)
An article was published at editorial of BJB in 2012 vol. 3 issue 1, page 3 entitled "Challenge of 21st Century to Integrate the Reproductive Technologies Concerning the Beginning of Human Life" written by Associate Editor of BJB. I would like to comment on article that the religions those have holy book from God have almost the same notion regarding the beginning of life. They are involved with biblical account of the creation of human and prefixed notion on procreation and families. From a bioethical point of view, religions seem to favor deontological models. It may hinder the proper ethical incorporation of reproductive technologies. Stewardship or divine providence leads to a fixed creational view, pessimist as basic attitude and dependence. On the other hand, other distinguished ethical models (consequentialism or utilitarianism) are "creativity", e.g. models of responsibility (personalism), models of caring (care ethics) etc. These models are anthropo-centric, optimistic, evolving creation (Created Co-Creator) and have open future. Therefore, it is crucial to understand how 21st century will integrate the new technologies concerning the beginning of human life. DOI: http://dx.doi.org/10.3329/bioethics.v3i2.11703 Bangladesh Journal of Bioethics 2012; 3(2):31-34